2019
DOI: 10.1016/j.jvs.2018.01.071
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of revascularization outcomes of infrainguinal chronic limb-threatening ischemia

Abstract: Background: The optimal strategy for revascularization in infrainguinal chronic limb-threatening ischemia (CLTI) remains debatable. Comparative trials are scarce, and daily decisions are often made using anecdotal or low-quality evidence.Methods: We searched multiple databases through May 7, 2017, for prospective studies with at least 1-year follow-up that evaluated patient-relevant outcomes of infrainguinal revascularization procedures in adults with CLTI. Independent pairs of reviewers selected articles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 17 publications
0
34
0
1
Order By: Relevance
“…Most current reconstructive procedures consist of interposition of the vessel defect with autologous or synthetic grafts because en bloc resection usually necessitates resection of a long segment of vessels. Previous review articles about obstructive arterial disease demonstrated that graft selection could influence the long-term limb-salvage rate, and autologous graft is superior to synthetic graft in patency (Almasri et al, 2018;Klinkert, Post, Breslau, & van Bockel, 2004). However, in sarcoma surgery in contrast to obstructive arterial disease, there are some specific situations, such as requirement of a relatively short graft, not atherosclerotic artery, and postoperative formation of arterial collateral.…”
Section: Discussionmentioning
confidence: 99%
“…Most current reconstructive procedures consist of interposition of the vessel defect with autologous or synthetic grafts because en bloc resection usually necessitates resection of a long segment of vessels. Previous review articles about obstructive arterial disease demonstrated that graft selection could influence the long-term limb-salvage rate, and autologous graft is superior to synthetic graft in patency (Almasri et al, 2018;Klinkert, Post, Breslau, & van Bockel, 2004). However, in sarcoma surgery in contrast to obstructive arterial disease, there are some specific situations, such as requirement of a relatively short graft, not atherosclerotic artery, and postoperative formation of arterial collateral.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, adverse events occurred in 9% of patients, mainly access-related and peri-procedural mortality was 0%, compared to a roughly 3% mortality rate and 20% major complication rate of infra-inguinal bypass (28–30). Furthermore, in clinical research, the mortality rate of patients with intermittent claudication is 2.5 times higher than age-matched controls, while patients with CLI present a mortality rate as high as 20% the first year after diagnosis (4,10).…”
Section: Discussionmentioning
confidence: 54%
“…Recent meta-analyses demonstrated high primary, assisted primary, and secondary patency rates after bypass surgery. 8,9 However, despite the difference in anatomic patency rates, the survival, limb salvage, and amputation-free survival rates have been comparable between the 2 treatment methods. 8-11…”
Section: Introductionmentioning
confidence: 99%